2014
DOI: 10.1103/physrevb.90.085141
|View full text |Cite
|
Sign up to set email alerts
|

First-principles description of charge transfer in donor-acceptor compounds from self-consistent many-body perturbation theory

Abstract: We investigate charge transfer in prototypical molecular donor-acceptor compounds using hybrid density functional theory (DFT) and the GW approximation at the perturbative level (G 0 W 0 ) and at full self-consistency (sc-GW ). For the systems considered here, no charge transfer should be expected at large intermolecular separation according to photoemission experiments and accurate quantum-chemistry calculations. The capability of hybrid exchange-correlation functionals of reproducing this feature depends cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 33 publications
(58 reference statements)
6
81
0
Order By: Relevance
“…In this approach, α is determined by requiring that the self-energy correction to the HOMO level within the G 0 W 0 approximation [11] is minimized. Eventually, this also fixes the starting point dependence of the perturbative GW approximation [12][13][14]. the local exchange potential in the PBE approximation [6].…”
Section: Introductionmentioning
confidence: 92%
“…In this approach, α is determined by requiring that the self-energy correction to the HOMO level within the G 0 W 0 approximation [11] is minimized. Eventually, this also fixes the starting point dependence of the perturbative GW approximation [12][13][14]. the local exchange potential in the PBE approximation [6].…”
Section: Introductionmentioning
confidence: 92%
“…(8) predicted Δ > 0, with ε TCNQ LUMO ¼ −4.32 and ε TTF HOMO ¼ −6.15 eV. The mixing fraction that minimizes the deviation from the straight-line error was shown to be 0.70 for TCNQ and 0.8 for TTF [77,78], not dissimilar from the values predicted by Eq. (8).…”
Section: Resultsmentioning
confidence: 87%
“…Marom et al 26 Table I compared with experimental results. the performance of a hierarchy of GW approximations for benzene, pyridine, and the diazines and compared the quasiparticle spectrum with PES. Caruso and co-workers [27][28][29] developed an all electron implementation of self-consistent GW (sc-GW ) with localized basis functions and showed that it is more accurate than other approximations lower in GW hierarchy. They applied sc-GW on five molecules relevant for organic photovoltaics 28 obtaining an average error of 0.4 eV (maximum error 1.2 eV).…”
Section: Applicationsmentioning
confidence: 99%
“…Those calculations suffer from a strong initial state dependence and the good agreement found could be just fortuitous. In this context, self-consistent GW [27][28][29] was found to systematically improve ionization energies and total energies of closed shell systems. The single electron spectral properties are in very close agreement with experiment avoiding the starting-point dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation